Análisis descriptivo del Currículo de formación del docente de Física, frente al Currículo del Bachillerato General Unificado - Morocho Cruz, Rocío Alicia (2023)
The main objective of the research study entitled "Descriptive analysis of the Physics teacher training curriculum, compared to the curriculum of the Bachillerato General Unificado", proposed as a general objective to analyze the Physics teacher training curriculum in the career of Pedagogy of Experimental Sciences, Mathematics and Physics, compared to the curricular contents of the Bachillerato General Unificado: Mathematics and Physics, compared to the curricular contents of the Unified General Baccalaureate, an observation sheet was used to contrast the contents of the Physics curriculum in the Unified General Baccalaureate with the contents of the Physics curriculum in the Experimental Sciences Pedagogy Degree: Mathematics and Physics, with a quantitative approach, the design is non-experimental, documentary or bibliographic type, descriptive level, the population consists of numbers of physics curriculum content both high school and career, it is concluded that the Physics teacher training curriculum if it covers the needs of the curriculum of the baccalaureate, It is suggested that a more detailed analysis of the topics and subtopics required in the Unified General Baccalaureate should be carried out, as these are specifically related to astrophysics.